Study of anti-corrosion and anti-wear properties on superhydrophobic aluminium alloy surfaces. Issue 15 (13th October 2018) - Qiu, Rongxian; Wu, Zhilin; Xu, Jinkai
ABSTRACT: To improve the wear and corrosion resistance of aluminium alloys in salt environments, we produced superhydrophobic surfaces via high-speed electrical discharge machining. The specimens were characterised using a scanning electron microscope and a laser scanning confocal microscope and through contact angle (CA) measurement, measurement of electrochemical corrosion at an electrochemical workstation and wear testing. Results showed that the superhydrophobic specimens had a water CA of 151.5°. The corrosion of the as-obtained superhydrophobic specimens was significantly reduced by more than 50%, indicating their excellent anti-corrosion properties. The wear of as-obtained superhydrophobic specimens were reduced by approximately 10–35% in dry conditions and by approximately 45–85% in 3.5% NaCl solution, revealing their excellent anti-wear properties in both dry and salt environments.